Pengembangan Disiplin Diri Melalui Kegiatan Pramuka Baris Berbaris di Sekolah Menengah Pertama - Yani, Muhammad Turhan; Purba, Elsa Riska; Parawansyah, Aura Zannuba; Solagratia, David; Pratama, Jogis Nur (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the contribution of the PBB training (PBB) in the Scouting activities to the formation of self-discipline and character of students at the Junior High School (SMP) level. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation studies. The results of the study indicate that the implementation of PBB is able to instill the values ​​of discipline, responsibility, leadership, cooperation, and self-regulation in students. This activity also has a positive impact on student behavior outside of Scouting activities, including in academics and socially. This finding strengthens that PBB training is not just a physical activity, but an effective and contextual character education strategy in supporting the goals of the Merdeka Curriculum and the formation of the Pancasila Student Profile. Therefore, this activity needs to be continuously developed and supported as an integral part of the character building program in schools.